Faktor yang mempengaruhi pembiayaan perbankan syariah di Indonesia: MODEL ECM - Ardana, Yudhistira (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
This study aims to determine the factors that influence the financing of Islamic banking inIndonesia. This study is examines BI rate, BOPO, CAR, FDR, Inflation, NPF, Exchange Rate andFinancing of Islamic Banking in Indonesia. The data in this study is secondary data from January2013 to September 2017. The data is analysed using the Error Correction Model and processedby eviews. The results of this are the variables that influence the short-term financing of Islamicbanks are BOPO and FDR, while the variables BI_rate, CAR, inflation, NPF and Exchange rateshave no effect. Furthermore, the variables that influence the long-term financing of Islamic banksare BI_rate, BOPO, CAR, FDR and inflation, while the NPF and exchange rate variables haveno effect.